The leadership types appropriate to different levels of management in the South African railway industry - Pillay, Theophilus (University of the Witwatersrand, Johannesburg, 2023)
The South African railway industry run by two state-owned entities, PRASA and Transnet have embarked on their Industry 4.0 strategy. It is a strategy that looks to reimagine the railway sector, the culture and its operations. The intent is to take SA and Africa to compete globally, and proudly take South African rail into this new digital platform. It is at the helm of these changes that organisations will need to adopt the state- owned entities strategy to remain competitive, producing railway solutions productively and efficiently to feed into the entities plans. One such organisation is Alstom International a rolling stock multinational that has been awarded the largest tender in South African history to produce the new Metrorail fleet for the state-owned entities. This research looks at one of Alstom International’s manufacturing subsidiaries in SA that produces railway solutions for the state-owned entities. It’s on the basis of the magnitude of the project that the study will consider the subsidiary to represent the railway industry of SA and will from this point onwards be referred to as the ‘organisation.’ There is a knowledge gap existing into the type of leadership behaviours that are needed to impact followers motivation and organisation’s success, which has become a major concern for the railway industry of SA. The purpose of this study was to investigate how and why transformational (TL) and transactional(TR) leadership behaviours can be used to fill this gap. HR and railway organisational practitioners will use this knowledge for improved recruitment practises and leadership development training. The study adopted a qualitative approach with semi-structured interviews conducted with 16 purposefully selected managers from the manufacturing organisation ranging from lower, middle to senior management. Thematic deductive analysis was conducted to determine the leadership behaviours used through the established transactional and transformational themes. Observations of the interactions between leaders and followers at various management levels were also done at the organisation to gather more data. The findings showed that transactional leadership behaviours were found to be the main style used by leaders. Transactional leadership behaviours were based on a strategy of compliance to Alstom International and also developed as the intent was to cut costs in manufacturing railway components. Transformational leadership behaviours were seen at upper 2 management levels, while transactional leadership behaviours were noted at lower management levels. Transformational leadership behaviours still had an augmenting role to play with blue collars to remove initial resistant because of past hurts caused by a fluctuating industry prone to retrenchments. It was found that the strategy of the organisation played a major role in the type of leadership behaviours used. The originality of the work is based on its South African railway context
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Transformational; Transactional leadership; Railway industry; Behaviour; UCTD; SDG-8: Decent work and economic growth